HOW CULTURE DISCIPLINE, WORK SUPERVISION AND COMMUNICATION ON EMPLOYEE PERFORMANCE - Muhammad Irfan Nasution; Windi Lestari (RADJA PUBLIKA, 2022)
This study aims to determine and analyze work discipline, work supervision, and communication on employee performance at the Forestry Service Office of North Sumatra Province. The approach used in this study is associative. In contrast, the population in this study is employee performance employees at the Forestry Service Office of North Sumatra Province, 666 employees; using the slovin formula, a sample of 87 people was obtained. The data analysis technique in this study used multiple linear regression analysis. The study results prove that simultaneously and partially, work discipline, work supervision, and communication significantly affect employee performance at the Forestry Service of North Sumatra Province. The implication of this research is on the communication variable, where communication is essential and very needed for employees so that there are no mistakes in the work being done, which causes a decrease in employee performance.